POTENTIAL INSTRUMENTS FOR COMMUNITY NURSES TO MEASURE CONDUCT PROBLEMS OF MIDDLE ADOLECENTS: A SYSTEMATIC REVIEW - Fauzan Saputra; Jintana Yunibhand (Poltekkes Kemenkes Bengkulu, 2022)
Conduct problems are prevalent in middle adolescents. There are many available instruments that can be used to measure conduct problems. However, limited information is available regarding which instruments are more suitable for this population in the community. This study aimed to investigate frequently used instruments to evaluate conduct problems in regard to their purposes and psychometric properties. This systematic review design study was performed from August 2021 to March 2022 to search for published articles from five databases, such as ProQuest, PubMed, PsycINFO, Science Direct, and Scopus. The PRISMA guidelines were applied to report the selection process of articles. The quality of the selected articles was evaluated by critical appraisal tools of the Joanna Briggs Institute (JBI). Of 7254 records, 23 studies met the inclusion criteria and were reviewed for psychometric properties. Findings indicated that there were nine instruments used in 23 studies for conduct problems among middle adolescents in the community, with the following purposes such as screening, assessment, clinical diagnosis, and outcome evaluation. The coefficient of Cronbach’s alpha of the instruments varies in the range of .53 to .95. Meanwhile, 65% of the studies were reported to use the Strengths and Difficulties Questionnaire – Conduct Problems (SDQ-CP), especially for screening, assessment, and outcome evaluation. It is suggested for community nurses use SDQ-CP to examine and evaluate conduct problems for middle adolescents who visit public health service facilities in the community.